An Analytical Study of Costs and Returns of Citrus Honey in Lattakia Governorate in Syria - Alio , Mahmoud (Latakia University Journal -Biological Sciences Series, 2013)
This study was conducted on a number of private apiaries in Lattakia Governorate in Syria which is one of the most important areas for beekeeping. The study investigated the costs and returns of beehives, and estimated some economic parameters using the descriptive economic analysis. Using a questionnaire, the data was collected from a sample of 20 apiaries. The data was then analyzed using appropriate statistical programs. Results showed that the annual total cost for a productive beehive was 3879.2 Syrian pounds, the annual return was 8650 Syrian pounds, and the annual profit was 4770.8 Syrian pounds. The results also showed that the net costs for royal jelly production was 3027.8 Syrian pounds, the net profit was 3722.7 Syrian pounds, and the net relative income was 122.99%. Results, moreover, indicate that the rent coefficient was 139.25%, the profitability coefficient was 122.98% in relation to production costs, the economic efficiency was 2.23, and the capital refunding period was 2.24 years.